Penerapan Pembelajaran Sains Berdifferensiasi di Islamic School Al-Hidayah, Perth Hedley St, Bentley, Western Australia 6102 - Laliyo, Lukman Abdul Rauf; Musa, Weni J.A; Panigoro, Citra; Kurniawati, Erga (Universitas Negeri Gorontalo, 2025)
The aim of this service article is to report the results of a study on the implementation of differentiated science learning at Al-Hidayah Islamic School, Perth, Hedley St, Bentley, Western Australia 6102. The focus is on identifying the challenges and successes of implementing this approach in an educational environment based on Islamic values. Al-Hidayah integrates the Walker Learning model, which accommodates students' learning styles, interests, and readiness through diagnostic assessment, flexible grouping, and the use of technology. This approach not only facilitates increased student engagement and motivation but also creates an inclusive and adaptive environment that embraces diversity. The research shows that differentiated learning can be a solution to overcome barriers in the Indonesian education system and offers a model that can be applied in Islamic schools with adjustments to the local context. These findings also provide recommendations regarding curriculum development, teacher training, and the use of technology to enhance the effectiveness of science learning in Indonesia. Thus, this study makes an important contribution to the development of learning that is responsive to the individual needs of students.